TEACHERS’ PERSPECTIVES ON THE FAMILY BACKGROUNDS OF CHILDREN AT RISK - Leroy, Carol; Symes, Brent (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2001)
ABSTRACT. This paper focuses on a qualitative study that investigated beliefs held by four teachers in high poverty communities about the family backgrounds of children they considered to be at risk for failure in school and later in life. Results indicated that the presence of child abuse in the home, alcoholism, and single or absent parents were the most frequently mentioned family risks thought by the teachers to be affecting specific children in their classrooms. However, the teachers also expressed uncertainty about the level of their understanding of families and about the nature of cause-and-effect relationships between familial factors and outcomes. Further, while the teachers saw familial difficulties as risks for children, they also highlighted the importance of systemic problems such as the lack of support for families in poverty and the differential responsiveness of schools to the more affluent and powerful parents. They also seemed to empathize with single parents, and believed that the cultural backgrounds of Indian and Métis students were a source of strength for Aboriginal children when they were at risk. RÉSUMÉ. Cet article décrit une étude qualitative sur les croyances qu’entretiennent quatre enseignants de collectivités très pauvres relativement aux antécédents familiaux des enfants qu’ils jugent «à risque», à savoir en voie d’échec à l’école, puis dans la vie active, et plus tard dans la vie. Les résultats démontrent que, parmi les facteurs familiaux de risque affectant des élèves de leur propre classe, les enseignants mentionnent le plus fréquemment l’alcoolisme, les sévices subis par les enfants au foyer familial, l’absence d’un parent voire des deux parents. Toutefois, les enseignants reconnaissent leurs incertitudes quant au niveau de compréhension qu’ils ont des familles et quant à la nature des relations causales entre les facteurs familiaux et les résultats scolaires. Par ailleurs, même si les professeurs considèrent que les difficultés familiales sont des facteurs pour les enfants, ils soulignent également l’importance de problèmes systémiques comme le non-soutien des familles pauvres et la réceptivité différente des écoles face aux parents plus influents et puissants. Ils semblent également empathiser avec les parents célibataires et sont d’avis que les antécédents culturels des élèves indiens et métis sont une source de dynamisme pour les enfants autochtones à risque.